TINGKAT KEPERCAYAAN DIRI DENGAN MOTIVASI BERPRESTASI ATLET PETANQUE DI SULAWESI SELATAN - Nur Indah Atifah; Hasmyati Hasmyati; Ilham Azis; Sufitriyono Sufitriyono; Hasyim hasyim (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2022)
The purpose of this study was to determine the relationship between the level of self-confidence and achievement motivation of Petanque in South Sulawesi. The research method used in this research is quantitative research with correlational method. The object of this research is all petanque athletes in South Sulawesi Province. Data collection techniques in this study used a questionnaire about self-confidence and achievement motivation of athletes. Data analysis used quantitative descriptive test. The results showed that the South Sulawesi petanque athletes had self-confidence in the high category and achievement motivation was in the medium category. the results of hypothesis testing there is a relationship between self-confidence and motivation to achieve, from the resulting significance value of 0.012 <0.05, which means there is a significant relationship. It can be concluded that the level of self-confidence with the motivation of Petanque Athletes in South Sulawesi has a significant relationship.